NMR Study of Non-Equilibrium State of Fullerene C60 in N-Methyl-2-Pyrrolidone - Karpenko, O.B.; Trachevskij, V.V.; Filonenko, O.V.; Lobanov, V.V.; Avdeev, M.V.; Tropin, T.V.; Kyzyma, O.A.; Snegir, S.V. (Ukrainian Journal of Physics, 2012)
The results of 1H~NMR researches concerning the interaction between fullerene С60 and N-methyl-2-pyrrolidone (NMP) molecules in an as-prepared solution are reported. By comparing the spectra for pure NMP and the С60-NMP system, system the formation of a complex between fullerene and solvent molecules is revealed, which is responsible for the time-dependent solvatochromic effect discovered earlier. Different magnitudes of chemical shifts for α-, β-, γ-, and α'-protons in the NMP molecules allowed a hypothesis to be put forward that the interaction in the С60-NMP system occurs through the formation of a donor-acceptor bond between the keto-group of an NMP molecule and a fragment of a С60 molecule. The results of quantum chemical simulation for the С60 · NMP complex with a stoichiometric composition of 1:1 testify to a redistribution of the electron density over the system of bonds in an NMP molecule induced by a С60 molecule.